Sosialisasi Alat Bakar Sampah Minim Asap Pada Masyarakat Desa Malangsari - Ardiatama Iedha Aradhea; Angelita Ramadhani; Wahyudin Wahyudin (KREATIF: Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
This research aims to explore the effectiveness of socialization regarding the application of low-smoke waste burning equipment in the Malangsari Village community in an effort to reduce the impact of air pollution. Waste is often considered trivial, even though waste is something that humans should pay attention to. Misuse of waste can violate the law regulated in Law Number 32 of 2009 concerning Environmental Protection and Management. The research method used is a qualitative approach with data collection techniques through observation, observation and documentation. The information collected is then analyzed using content analysis. The results of the research show that the socialization of smoke-free waste burning equipment has succeeded in increasing the awareness of the Malangsari Village community about the importance of environmentally friendly waste management. Socialization activities took place indoors and outdoors on Thursday, January 26 2024. Through counseling, demonstrations and practical training, the community understood how to make and use smoke-free waste burning devices correctly. Apart from that, there was also an increase in the active participation of the Malangsari Village community in the socialization of low-smoke waste burning tools. Keywords: Tools, Trash, Socialization.